Pengembangan Lembar Kerja Siswa Berdasarkan Teori Apos (Action, Processe, Object, Shceme) untuk Meningkatkan Efektivitas Pembelajaran Matematika - Husnul Khatimah; Kamid Kamid; Jefri Marzal (Universitas Jambi, 2015)
The objectives of the study are (1) to produce student worksheets based on APOS Theory for Math lessons in Class X Senior High School which is in line with the 2013 Curriculum; (2) to evaluate the effectivity of the student worksheets based on APOS Theory, in terms of the activity and result of learning Matrix. The results of the study are (1) the development of the worksheets (according to APOS Theory) were carried out through five stages, namely, analysis, design, development, implementation and evaluation; (2) the assessments performed by media experts, material specialists and subject teachers showed that the worksheets developed are feasible and could be used for students of Class X Senior High School; (3) the responses given by the students towards the worksheets were good; (4) the effectivity of the learning was elevated; it was shown by the increased learning activities of the students and the higher average score of the test (87.14), compared to the minimum criterion of completeness of 75.